Pengaruh Tingkat Pengetahuan Ibu Hamil dengan Tanda Bahaya Kehamilan di Praktik Bidan Bersama Bina Ibunda 2023 - Renanti, Malia; Hidayat, Reni; Sofia, Lina (Media of Health Research, 2024)
Warning Signs of Pregnancy are symptoms that can indicate danger during pregnancy, which, if undetected, may lead to the death of both mother and fetus. Therefore, it is essential for pregnant women to recognize these warning signs so they can immediately seek help from the nearest healthcare facility if they experience any of them. The purpose of this study is to assess the level of knowledge among pregnant women regarding pregnancy warning signs at the Bina Ibunda Midwife Joint Practice in 2023. The variables studied include the level of knowledge about various pregnancy warning signs, including those related to preeclampsia, bleeding, premature rupture of membranes, hyperemesis gravidarum, and other warning signs. The research design used is a descriptive study. The population consists of pregnant women at the Bina Ibunda Midwife Joint Practice in 2023, with a sample size of 100 pregnant women. Sampling was conducted in September 2022 using Consecutive Sampling techniques. The results show that most of the pregnant women 84% have a good level of knowledge about pregnancy warning signs, while 16% have a moderate level of knowledge. Specifically, 67% of the women are well-informed about preeclampsia warning signs, 76% have good knowledge of bleeding warning signs, 86% are well aware of premature rupture of membranes, 59% understand the warning signs of hyperemesis gravidarum, and 67% are well-versed in recognizing other warning signs. The conclusion from this study is that the majority of pregnant women have a good level of knowledge about the warning signs of pregnancy.